Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1016/s0140-6736(03)13413-7
|View full text |Cite
|
Sign up to set email alerts
|

Lung pathology of fatal severe acute respiratory syndrome

Abstract: SARS is associated with epithelial-cell proliferation and an increase in macrophages in the lung. The presence of haemophagocytosis supports the contention that cytokine dysregulation may account, at least partly, for the severity of the clinical disease. The case definition of SARS should acknowledge the range of lung pathology associated with this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

64
1,022
9
29

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 997 publications
(1,124 citation statements)
references
References 21 publications
64
1,022
9
29
Order By: Relevance
“…Thus, the prominent accumulation of interstitial and alveolar M in the lungs of patients severely affected by SARS has raised the possibility that pulmonary M could be one of the primary targets of SARS-CoV (8). However, the rarely detected viral genome and complete absence of viral Ags or viral particles in pulmonary M , as revealed by subsequent studies, in which the cellular and tissue distribution of SARS-CoV was examined in postmortem lung tissues by in situ hybridization and immunohistochemistry, strongly suggest that they might function as scavengers rather than as the prime targets for this virus (9,43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the prominent accumulation of interstitial and alveolar M in the lungs of patients severely affected by SARS has raised the possibility that pulmonary M could be one of the primary targets of SARS-CoV (8). However, the rarely detected viral genome and complete absence of viral Ags or viral particles in pulmonary M , as revealed by subsequent studies, in which the cellular and tissue distribution of SARS-CoV was examined in postmortem lung tissues by in situ hybridization and immunohistochemistry, strongly suggest that they might function as scavengers rather than as the prime targets for this virus (9,43).…”
Section: Discussionmentioning
confidence: 99%
“…SARS is a highly contagious and life-threatening respiratory disease with the lower respiratory tract (e.g., the lungs) as its main target of the pathogenic process (3,8,9). Immunopathological examination of postmortem lung tissues from SARS patients revealed diffuse alveolar damage with prominent pneumocytic hyperplasia and accumulation of alveolar and interstitial macrophages (M ), as well as other pathological manifestations characteristic of acute respiratory disease syndrome resulting from massive inflammatory responses in the lungs.…”
mentioning
confidence: 99%
“…It has been reported that some patients experience deterioration during the second week of illness despite a decreasing viral load and it has been suggested that there may be an immunopathologic component contributing to lung damage (13)(14)(15).…”
mentioning
confidence: 99%
“…Sin embargo, su uso en diversas series se ha asociado a un mejor pronóstico, especialmente cuando han sido utilizados entre los días 6 a 8 de la enfermedad. Nichols et al 35 realizaron estudios postmortem en seis pacientes que fallecieron debido al SARS, y encontraron proliferación hiperplásica epitelial asociada con hemofagocitosis. La presencia de este fenómeno se ha asociado clínicamente a una regulación alterada de la cascada inflamatoria de las citocinas, lo cual podría considerarse como un marcador que sugiere cómo la utilización clínica de esteroides podría ser de gran importancia.…”
Section: Tratamientounclassified
“…La presencia de este fenómeno se ha asociado clínicamente a una regulación alterada de la cascada inflamatoria de las citocinas, lo cual podría considerarse como un marcador que sugiere cómo la utilización clínica de esteroides podría ser de gran importancia. 35 * Hong Kong, República Popular de China, Taiwán.…”
Section: Tratamientounclassified